Book review: Keil, R. 2018: Suburban Planet: Making the World Urban from the Outside In. Urban Future Series. (July 2019) - Wu, Camille S.
Keil, R. 2018: Suburban Planet: Making the World Urban from the Outside In. Urban Future Series . Cambridge: Polity Press. ix + 258 pp. US$64.95 (Hardcover), US$26.50 (Paperback). ISBN: 13: 978-0745683126 (Hardcover). ISBN: 10: 0745683126 (Paperback)